2010
DOI: 10.1007/s00284-010-9774-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Alleles of Toxin Co-Regulated Pilus A Gene (tcpA) from Environmental Isolates of Vibrio cholerae

Abstract: Vibrio cholerae is causative agent of life threatening diarrheal disease, cholera. The toxin co-regulated pilus (TCP) is a critical colonization factor of V. cholerae and it also serves as receptor for CTXФ. In this study, we describe nucleotide sequence of four novel alleles of tcpA gene from toxigenic and non-toxigenic V. cholerae isolated from environmental sources. The phylogenetic analysis of tcpA revealed that it is related to tcpA of newly emerged O1 strain and unrelated to tcpA of wild type (classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
4
12
1
Order By: Relevance
“…S1). The Mexican and Chinese strains with analogous tcpA sequences formed a separate cluster to the 10 clusters for tcpA alleles reported to date (11). Overall, results of the analysis clearly indicate that tcpA of Mex-2058 and Mex-3065 have a lineage distinct from the seventh pandemic ET.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…S1). The Mexican and Chinese strains with analogous tcpA sequences formed a separate cluster to the 10 clusters for tcpA alleles reported to date (11). Overall, results of the analysis clearly indicate that tcpA of Mex-2058 and Mex-3065 have a lineage distinct from the seventh pandemic ET.…”
Section: Resultsmentioning
confidence: 57%
“…Like CTXΦ, TCP is biotype-specific, with two distinct alleles of tcpA encoding the major protein "pilin" (10,11). In Mexico, the TCP variant of V. cholerae O1 strains carries a tcpA sequence that is different from tcpA types reported to date, including CL and ET (10,11), although an analog of the Mexican type tcpA deposited in GenBank is from a nontoxigenic O1, reportedly isolated in 2006 from China. V. cholerae O1 strains from Mexico carrying the variant tcpA are nontoxigenic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we cannot verify the absence of tcpA and tolQRA genes by PCR alone. As of 2011, Kumar et al [14] reported that there were several variants of the tcpA gene which could be classified into 10 genetically distinct clusters in V. cholerae and V. mimicus. Therefore, it remains to be determined whether these isolates carry tcpA and tolQRA by not PCR but southern blotting analysis.…”
Section: Resultsmentioning
confidence: 99%